Comparison of Lactic Acid Bacteria and Bifidobacteria from Honey Stomachs and Honeycombs of Giant Honeybee (Apis Dorsata) in Kedah and Terengganu, Malaysia - Tajabadi, Naser (2010)
The isolation and identification of lactic acid bacteria (LAB) in the honey stomachs and honeycombs of Giant honeybee (Apis dorsata) from different areas in Malaysia were performed to prospect for beneficial bacteria or probiotics. Honey stomach samples of honeybee and honeycomb filled with honey were collected from Apis dorsata colonies in different bee trees from the rainforests of Pedu Lake in Kedah state and the agricultural region of Marang in Terengganu, Malaysia. The isolates were cultured anaerobically in different media of MRS agar, MRS broth and TPY broth at 37°C. Three hundred and fourteen isolates were obtained and identified based on biochemical tests, as LAB. In addition, 20 uncultured samples were identified as Bifidobacterium by using the nested polymerase chain reaction (PCR). The 16S rRNA genes from extracted DNA of bacterial colonies were amplified with PCR and nested PCR using universal primers of 27F and 1492R for LAB, and for Bifidobacterium two pairs of genus specific primers (Lm26 paired with Lm3 and Bif164-F paired with Bif662-R) were utilized. All bacterial 16S rRNA genes were sequenced and entrusted in GenBank and were given specific accession numbers. Phylogenetic analysis of the 16S rRNA sequences showed that the novel LAB and Bifidobacterium isolates could be grouped into four different phylotypes. They were found to be composed of 37 Lactobacillus, 6 Enterococcus, 2 Bifidobacterium and 1 Weissella phylotypes. The results showed that among 334 isolates and sequences, Lactobacillus spp with 64.97% were found to represent the most common LAB in Apis dorsata honey stomachs and honeycombs followed by Enterococcus spp with 28.74%, Bifidobacterium with 5.99% and the rest 0.3% Weissilla. Overall, the predominant lactobacilli species found in the total samples constituting approximately 40.55% of Lactobacillus kunkeei. Lactobacillus kunkeei (YH-15) related sequences (88) were the predominant lactobacilli followed by 33.18% of other Lactobacillus sp with related sequences (72). In honey stomach samples, the prevalence of Lactobacillus spp. was 53.21%. Interestingly, the predominant Lactobacillus species found in all honey stomach samples was Lactobacillus plantarum. (30.12%) followed by Lactobacillus pentosus (27.71%), Lactobacillus kunkeei (22.89%), Lactobacillus sp (15.66%), Lactobacillus vermiform (2.41%) and Lactobacillus fermentum (1.21%). Samples from the honey-filled honeycomb showed a prevalence of Lactobacillus spp. at 75.28 %. The predominant Lactobacillus species from all honeycomb samples constituting of Lactobacillus kunkeei (51.49%), Lactobacillus sp (44.03%) and Lactobacillus alvei (4.48%). Enterococcus spp. was isolated from every honey stomach (40.38%) and honeycomb (18.54%) of Kedah and Terengganu samples. The predominant Enterococcus species from all honey stomach and honeycomb samples, constituting approximately 88.54% of total isolated Enterococcus spp., was Enterococcus sp and the rest was Enterococcus faecalis (11.46%). Whereas, Bifidobacteria and Weissilla account for about 5.99% and 0.3% respectively.